Faya dayi - Basinski, William 1958-; Aniol, Adrian; Holstetter, Kaethe (The Criterion collection, 2022)
"A sublime work of personal vision, the debut feature by the Mexican Ethiopian filmmaker Jessica Beshir is a hypnotic documentary immersion in the world of Ethiopia’s Oromo and Harari communities, places where one commodity -khat, a euphoria-inducing plant once prized for its supposedly mystical properties—holds sway over the rituals and rhythms of everyday life. As if under the influence of the drug itself, Faya dayi unfurls as intoxicating, trance-state cinema, capturing intimate moments in the existence of everyone from the harvesters of the crop to people lost in its narcotic haze to a desperate but determined younger generation searching for an escape from the region’s political strife. The director’s exquisite monochrome cinematography—each frame a masterpiece sculpted from light and shadow—and the film’s time-bending, elliptical editing create a ravishing sensory experience that hovers between consciousness and dreaming." [criterion.com]